(3GdefJXes - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3edG eMeO egOi CbGHGjG s)
(3ChdgG (B:s
(3eMeO Hf GdUHGM bGd HfG CHh GdKfG TcQ GdYJVOi bGd dfG ONd YVO GdOhdI Edi HZOGO hbO ggddJ CgdgG bJdG hMQbG s
(3BNQgG (B:s
(3hGjGfG hLejY GdeSdejf hLeYfG hGjGge ai OGQ cQGeJg Je GdJGQjN GdefJXe ai CNHGQ GdGee s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1850s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs